Pengembangan Media Komik Matematika Berbasis Visual Pada Materi Kerucut dan Tabung Di Sekolah Dasar - Indra Murti Wulandari; Indri Anugraheni (Jurnal Ilmiah Wahana Pendidikan, 2021)
Education is a conscious and planned effort to shape civilized humans. Education is very important for a nation so that National development can run well and optimally according to Pancasila and the 1945 Constitution. The National Education System in article 3 states that national education functions to develop capabilities and shape the character and civilization of a nation with dignity in educating the nation's life (Depdiknas, 2003). Thus, national education aims to develop the potential of students to become individuals who believe and believe in God Almighty, have a noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens (Kemendikbud, 2013). Efforts to improve students 'mathematical communication can be done by using comic media to find out students' understanding of using visual-based comic media or textbooks. By using visual learning media because the learning media is able to show learning material in the form of a display, its presentation is simple and has a simple nature in its presentation, one of which is comics. In data collection and data analysis, researchers used Research and Development (R&D) techniques using the ADDIE development model.